Being There: Exploring Virtual Symphonic Experience as a Salutogenic Design Intervention for Older Adults - Faw, Meara H.; Buley, Taylor; Malinin, Laura Healey (Frontiers in Psychology, 2021)
This co-design study examined salutogenic potential of mobile virtual reality (VR) experiences as an alternative to participation in a community-based symphonic engagement program (B Sharp), previously found to benefit people with dementia (PWD) and their informal caregivers. Six focus groups were conducted with sixteen adults aged 76 to 90; three participants had dementia, and two were informal spousal caregivers. No participants had prior VR experience. The study assessed the feasibility of replicating the community-based-arts program in VR, with the goal of enhancing its salutogenic qualities (e.g., positive distraction, engagement, social connection). Video-recordings of participants while using a mobile head-mounted display (HMD) were analyzed using qualitative thematic analysis to compare perceptions of different virtual experiences, including replication or enhancement of B Sharp and a campus tour. Findings suggest participants had positive perceptions of enhanced VR experiences with no adverse effects, although PWD were less enthusiastic and HMD usability was complicated by eyewear use and comfort with technology. Participants reacted most favorably to the enhanced symphonic experience, where they were “virtually” onstage during the performance, suggesting unique experiences beyond what is possible in the real world have the greatest potential for deep immersion for older adults. Results suggest VR has strong potential to replicate and enhance salutogenic qualities of community-based programming by enabling greater access to experiences for older adults and by increasing enjoyment and engagement through experiences not otherwise feasible. Furthermore, this study illuminates advantages of a user-centered, co-design approach when developing VR experiences with community partners and older adults.